SEL programs promote students' wellbeing and relationships: teachers experiences in a qualitative evidence synthesis - Mangrio E.; Pettersson A.; Ivarsson A.; Ryk C.; Strömwall L. A; Kostenius C. (Cogent Psychology)
During the past decades there has been an increase in mental ill-health problems among children. Social-emotional learning (SEL) has shown promise to promote well-being by supporting children in developing abilities to cope with everyday difficulties. Structured SEL programs can be part of the school curriculum from early age. However, teachers' positive perceptions of the values of such programs are essential for program success. The aim of this evidence synthesis was to describe and understand teachers' experiences of providing SEL programs to students and their perceived effect on students' mental well-being. We followed the ENTREQ and PRISMA guidelines. Systematic searches were conducted and we included seven studies with a moderate level of methodological limitations. We conducted a thematic meta-synthesis, and confidence in the evidence was assessed with GRADE-CERQual. Teachers perceived that students developed a higher level of coping with their feelings and created improved relationships as a result of the SEL programs. As they received new tools to support students' well-being, teachers were positive to the programs. They noted, however, that the programs needed adaptation to the local context. To the best of our knowledge, this is the first meta-synthesis on the experiences among teachers on the impact of SEL programs on students' well-being. Notably, the results suggest that SEL programs could help teachers to attend to students' mental health. After conducting extensive searches for data, only studies from high-income countries were found. Therefore, further studies are needed within low-income countries in regard to SEL programs and experiences among teachers on students' mental wellbeing. It would also be beneficial to synthesize research on the students and their experiences on how SEL programs impact their mental well-being.